Trigeminal neuralgia. a retrospective survey of a sample of patients in Singapore and Malaysia - Loh, H.S.; Ling, S.Y.; Shanmuhasuntharam, P.; Zain, R.B.; Yeo, J.F.; Khoo, S.P. (Blackwell Publishing Inc., 1998)
This survey was undertaken to study the clinical features of trigeminal neuralgia in an Asian population. Demographic data of 44 patients treated at the Dental Faculty of the National University of Singapore and at the University of Malaya were reviewed. The results of the survey were analysed and comparisons made with those of Caucasian patients as reported in other studies where there was a general similarity in the clinical findings. Trigeminal neuralgia presented predominantly in females. Right-sided involvement occurred at a greater frequency, and the peak age at onset was between the sixth and seventh decades of life. The only significant variant in the present sample was the greater involvement of the mandibular branch of the trigeminal nerve rather than the maxillary division. In addition, there was a much greater representation from Chinese patients over Malays as compared with their ratios in the general population.